The impact of using community home-based elderly care services on older adults’ self-reported health: fresh evidence from China - He, Yang; Wei, Baojian; Li, Yushang (Frontiers in Public Health, 2023)
The study employs the Instrumental Variable technique and empirically investigates the relationship between the elderly's use of community home-based elderly care services (CHECS) and their self-reported health using data from the China Longitudinal Aging Social Survey from 2018. The findings indicate, firstly, that using CHECS considerably improves the elderly's self-reported health. Second, the heterogeneity test reveals that the effect is more pronounced for elderly people who are under the age of 80, have functional disabilities, are free of chronic diseases, have never attended school, reside in lower-income households, are single, rarely interact with their children, and live in central urban or city/county regions.Thirdly, the mechanism test reveals that the "social network effect" and "family care effect" are the key influence channels of using CHECS. An empirical foundation for the policy reform of community home-based care for seniors is provided by by this study with the limitations to discuss the other socioeconomic aspects such as family per capita income, and government health expenditure. The findings carry substantial implications for improving the health of older individuals and provide suggestions for establishing a socialized aged care system in China.